COMPARISON OF PERITUBAL INFILTRATION OF ROPIVACAIN AND PLACEBO IN PERCUTANEOUS NEPHROLITHOLAPAXY FOR POST OPERATIVE ANALGESIA AT SOETOMO HOSPITAL SURABAYA - Telussa, Arley Sadra; Hakim, Lukman; Soebadi, Doddy M (Indonesian Journal of Urology, 2018)
Objective: To observe the effects of ropivacain peritubal infiltration in reducing postoperative pain and analgesic requirements postoperatively in patients underwent percutaneous nephrolithotomy (PNL). Material & method: Double blind randomized controlled trial on 32 patients with renal stone who underwent PNL at Soetomo General Hospital Surabaya from February until August 2017, divided into 2 groups. Experimental group (A) who received peritubal infiltration of ropivacain pre-operative, and control (placebo) group (B) Evaluation using Wong Baker pain score 2 hour post operation, time from operation until first rescue analgesia, and total analgesia given in first 24 hours. Result: Mean age was 51.81 ± 9.13 and 49.31 ± 10.53 years in group A and B respectively. Mean operation time 49.31 ± 10.53 and 89.69 ± 17.74 hours in group A and B respectively. There was no significant difference in stone complexity, nephrostomy placement and stenting between two groups. There was no significant difference of Wong Baker pain score 2 hours post operation between group A and B (p 0.72). There was no significant difference in total analgesia in the first 24 hours between group A and B (p 0.48). The time of first rescue analgesia demand was significantly longer in the experimental group (p 0.00). Conclusion: Peritubal infiltration of ropivacain in percutaneous nephrolitholapaxy is safe and effective to prolong the need of first rescue analgesia in post operative pain management which result in patients convenience.